Gaya Pengurusan Konflik di Kalangan Pegawai Kumpulan Pengurusan dan Profesional: Satu Kajian Kes di Jabatan Ketua Pengarah Tanah dan Galian Persekutuan, Putrajaya - Noor Rashidah, Ramli (2011)
The purpose of this study was to investigate the conflict management styles among the group of management and professional officers in Department of General Director of Lands and Mines, Putrajaya, Malaysia. The focus of this research was on the differences of each variable for demographic factors and the relationship between personality dimension and conflict management styles. Out of 122 questionnaires distributed, a total of 104 questionnaires were returned and valid to process. The data was analyzed using Statistical Package for Social Science (SPSS) version 18.0. The finding showed that there was significant differences in demographic factors of age, highest educational level, marital status, years of service in government sector, and grade in current post in the ways of conflict management styles, however in term of gender, race and the number of customers that has to be entertained a day, the result showed that there was no significant differences impact. The Pearson Correlation was applied to investigate a correlation between independent variables of personality dimension and dependent variables of conflict management styles. The research proved that there was highly significant relationship in the perception of majority respondents for personality dimension and conflict management styles with r value of .535**. The result indicates that majority of respondents held an Extrovert personality (mean 3.70), Conscientiousness (mean 3.68), and Openness to Experience (mean 3.67),whereas for Agreebleness (mean 3.23) and Neuroticism (mean 3.20). Generally, the personality dimensions have a positive relationship with the conflict management styles but only Neuroticism personality represents a strong relationship with negative. The findings also showed that the most preferred conflict management styles that has been practices in this group of respondents was Compromise (mean 3.98), followed by Collaboration (mean 3.73), Accommodate (mean 3.66), Avoidance (mean 3.61) and Competition (mean 3.33).